The Influence of Leadership Style on Employee Performance at Perum Damri in Makassar - Rombe , Delvia Obed; Tandirerung , Ch. Jeane; Rasinan , Djusniati (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Study This aiming For analyze influence style leadership to performance employees at Perum Damri Makassar. Research methods used is approach quantitative with technique survey through questionnaire to 30 respondents from population as many as 30 employees ( sample) saturated ). Data were analyzed using Pearson correlation test and partial t-test . The results of the study show there is connection positive and significant between style leadership and performance employee with mark coefficient correlation (r) of 0.399 and significance of 0.029 (p < 0.05). The coefficient of determination (r²) of 15.9% indicates that style leadership explain part small variability performance employees , while the rest influenced other factors . The t-test produces t- value count of 2.301 > t- table 2.048 which indicates influence significant . In conclusion , style communicative , participative and motivating leadership​ own contribution in improvement performance . Research This recommend that management in a way consistent evaluate and develop practice leadership to improve performance organization in a way sustainable .